Quick spreading of the exotic amphipod Laticorophium baconi (Shoemaker, 1934): another small stowaway overlooked? - JOSÉ MANUEL GUERRA-GARCÍA; TRIANA REVANALES; PABLO SAENZ-ARIAS; CARLOS NAVARRO-BARRANCO; SOFÍA RUIZ-VELASCO; MARÍA PASTOR-MONTERO; JUAN SEMPERE-VALVERDE; SAHAR CHEBAANE; ALBERTO VÉLEZ-RUIZ; GEMMA MARTÍNEZ-LAIZ; MAR SANTOS-SIMÓN; JASMINE FERRARIO; et al. (Mediterranean Marine Science, 2023)
Studies of non-indigenous species (NIS) often tend to focus on medium and large-sized taxa with potential for remarkable ecological and/or economic impact, whereas the early detection of small invertebrates is often delayed due to taxonomic challenge, lack of consistent, standardised monitoring efforts and limited funding. This study represents the first records of the marine amphipod Laticorophium baconi (Shoemaker, 1934) in Morocco, Tunisia, Corsica (France), Italy, Greece, Egypt, Saudi Arabia and New Caledonia (France). Furthermore, it reports an expansion of its known distribution in Portugal (earliest and northernmost record for the country and first record for Macaronesia), Spain (earliest record for Atlantic and Mediterranean European waters), and Australia (first record for Indian Ocean). Recreational boating and commercial shipping, mainly through hull fouling and secondarily ballast waters, are proposed as vectors for introduction and secondary spread of L. baconi. The following traits, analysed during the present study, could contribute to its invasive potential: (i) quick and extensive spread of the species worldwide, (ii) high densities in marinas, harbours, hull fouling and other artificial habitats, including aquaculture facilities and floating debris, (iii) high ability for short-term colonisation of empty artificial niches, (iv) diet based on detritus suggesting an opportunistic feeding behaviour, and (v) population survival during seasonal fluctuations in different regions. Taxonomic expertise and scientific collaboration, based on multidisciplinary networks of experts, are crucial for the early detection, distribution updates, and risk assessment of small and overlooked stowaways in marine environments.